Processos hidrogeoquímicos envolvidos na salinização dos reservatórios Algodoeiro e Três Barras situados na região do baixo São Francisco no estado de Sergipe - Alencar, Nívia Raquel Oliveira (2020)
One difficulty encountered in the management of surface reservoirs is their vulnerability to natural and man-made factors that interfere with their characteristics, and one of the biggest problems to be faced is the salinization of waters, especially in semi-arid regions due to rainfall and intense evaporation. Research in hydrogeochemistry has sought to answer questions about the chemical changes that occur in waters subjected to successive evaporations. In this case, the mechanisms that control the salinization process of the Algodoeiro and Três Barras reservoirs located in the lower São Francisco region, state of Sergipe, were studied. For this, the parameters of temperature, pH, total dissolved solids, Na+ , K + , Ca2+, Mg2+, HCO3 - , SO4 2- and Cl- were used for the surface water samples collected in the periods of 1996, 2013, 2014, 2017 and 2018. To assess geochemical variations, multivariate statistics - Principal Component Analysis was used, with the main ionic ratios and evaporation simulations by the direct modeling tool of the PHREEQC software. The results showed that, according to the Gibbs diagram, evaporation-crystallization is the main mechanism that controls the salinization process of the reservoirs. Mostly, the waters of the Algodoeiro and Três Barras reservoirs were classified as sulfated-chlorinated-sodium by the Piper diagram, and with ―exceptionally high‖ risk of irrigation salinization, according to the USSL salinity diagram. The statistical analysis did not show differences between the seasonality of the reservoirs, the main component analysis divided the samples by the salinization content, with the Três Barras reservoir being more salinized. Through the ionic reasons, the presence of the dissolution of halite and a strong reverse ion exchange process between sodium and calcium were proven, with a minor contribution of the minerals calcite and dolomite. The PHREEQC modeling confirmed that evaporation was the main phenomenon responsible for the salinization of the reservoirs, concentrating sodium, chloride, sulfate and magnesium ions in water. Evaporation losses of 50% and 58% of water were found for the Algodoeiro and Três Barras reservoirs respectively. As salinization increased, calcite and dolomite supersaturation and precipitation were observed in the Algodoeiro reservoir, calcite subsaturation and dolomite supersaturation for the Três Barras reservoir. For both reservoirs, halite and gypsum remained subsaturated, in a constant process of dissolution.